2019
DOI: 10.1055/a-0990-9225
|View full text |Cite
|
Sign up to set email alerts
|

Predicting pathology on small bowel capsule endoscopy: a good FIT

Abstract: Background and study aims  Small bowel capsule endoscopy [SBCE) has an established role in investigating suspected small bowel bleeding [SSBB). Identification of a biomarker to predict pathology would maximize utility of this valuable diagnostic modality. This study aimed to investigate if fecal immunochemical test [FIT) could predict likelihood of small bowel pathology on SBCE. Patients and methods  Patients referred for SBCE to investigate anaemia or suspected small bowel bleeding were prospectively recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Judge et al found a statistically significant association between positive FIT (FIT >/= 45 µg Hb/g was considered positive) and pathology on SBCE (OR 12, 95% CI [2.8-51.9], p = 0.001). The sensitivity and specificity of positive FIT in predicting SBCE findings were 69 and 89%, respectively [13]. A negative FIT has also been shown to have a high negative predictive value for small-bowel lesions in this and other studies [13,14].…”
Section: Biomarkerssupporting
confidence: 54%
See 1 more Smart Citation
“…Judge et al found a statistically significant association between positive FIT (FIT >/= 45 µg Hb/g was considered positive) and pathology on SBCE (OR 12, 95% CI [2.8-51.9], p = 0.001). The sensitivity and specificity of positive FIT in predicting SBCE findings were 69 and 89%, respectively [13]. A negative FIT has also been shown to have a high negative predictive value for small-bowel lesions in this and other studies [13,14].…”
Section: Biomarkerssupporting
confidence: 54%
“…The sensitivity and specificity of positive FIT in predicting SBCE findings were 69 and 89%, respectively [13]. A negative FIT has also been shown to have a high negative predictive value for small-bowel lesions in this and other studies [13,14].…”
Section: Biomarkerssupporting
confidence: 54%
“…In recent years, new evidence has also emerged concerning the possible role of fecal occult blood testing (FOBT), either guaiac or immunochemical, as a filter test to select IDA patients for SBCE [77][78][79]. The meta-analysis by Yung et al [80] found, for all positive FOBT, sensitivity 0.60 (95 %CI 0.50-0.69), specificity 0.72 (95 %CI 0.52-0.86), and diagnostic OR 3.96 (95 %CI 1.50-10.4) for SB findings.…”
Section: Iron-deficiency Anemiamentioning
confidence: 99%
“…The study by Judge et al showed promise for the expanding role of Faecal immunochemical test (FIT) in the detection of small bowel lesions [16]. In this study of 51 patients, a positive FIT (≥45 μgHb/g) had a sensitivity of 69% in the detection of small bowel pathology.…”
Section: Editorialmentioning
confidence: 72%